Effect of adhesive strategy of universal adhesives in noncarious cervical lesions - an updated systematic review and meta-analysis - Krisha Doshi; M. S. Nivedhitha; Pradeep Solete; Delphine Pricilla Antony S; Arthi Balasubramaniam; Benoy Jacob; Riluwan Siddique (Nature Publishing Group, 2023)
Abstract Objective To determine the effect of adhesive strategy (total etch or self-etch) of universal adhesives in non-carious cervical lesions. Data source A search was made in PubMed, Scopus, Cochrane, Web Of Science, Open Gray, Clinical Registries. Data selection Randomized Controlled Clinical Trials, studies on non-carious cervical lesions restored using Universal Adhesives, and studies in which universal adhesives have been used in total etch and self -etch strategies were included in this systematic review. Data extraction A total of 17 articles were included in the systematic review and 13 in the meta-analysis. Meta-analysis was conducted to assess the clinical performance of NCCLs in terms of retention, marginal adaptation, marginal discoloration, secondary caries and post-operative sensitivity at 18, 24, 36 month follow-up using USPHS as well as FDI criteria, separately. Data synthesis Overall there was no significant difference between total etch and self etch adhesive strategies for any of the five outcome measures using either the FDI or the USPHS criteria. p > 0.05, 95% CI, I2 value of 0%. A strongly suspected publication bias in the retention domain was seen at 18 month follow up under FDI criteria. Conclusion Most universal adhesives show acceptable clinical performance. There is no significant effect of the adhesive strategy of universal adhesives on their clinical performance according to the results of our meta-analysis.